Library management system using RFID technology / Muhammad Khairani Abdul Rahman, Siti Nor Aisah Muhammad and Siti Nur Muslihah Muzaffar - Abdul Rahman, Muhammad Khairani; Muhammad, Siti Nor Aisah; Muzaffar, Siti Nur Muslihah (2018)
Radio Frequency Identification (RFID) is a new generation of Auto Identification and Data collection technology which helps to automate business processes and allows identification of large number of tagged objects like books using radio waves, RFID based library management system would allow fast transaction flow for the library and will prove immediate and long term benefits to library traceability and security. This project is developed to replace the conventional library management system that designed and extremely difficult to handle for bigger library. This system is provided an efficient for leading books using combination of RFID sensor ARDUINO. ARDUINO is used as a main microcontroller for to operate this whole management system. RFID will manage and control all the information of the library and the problems will be solved.